Capital Structure Optimization of Beauty Brands in International Market Expansion: The Integration of Financing Options and Market Entry Strategies - Deng Keer (SHS Web of Conferences)
This study explores the synergistic effects of capital structure and market entry strategies of global cosmetics brands. In view of the differentiation between the stagnation of mature markets and the rapid growth of emerging markets in the Asia-Pacific region, this paper reveals the dynamic matching mechanism between financing methods (debt, equity, and hybrid) and market entry models (mergers and acquisitions, joint ventures, and greenfield investment) through a longitudinal analysis of the financial data of multinational beauty groups. The results show that the suitability of capital structure and market entry strategy significantly affects the success rate of expansion-mature markets prefer debt financing and wholly-owned models, while emerging markets need to adopt hybrid financing and joint venture strategies to diversify risks. Dynamic capital structure adjustment optimizes resource allocation and increases market share retention by 22%. The case study shows that the asset-lightening strategy (franchising) has achieved rapid penetration in the Southeast Asian market, while the wholly-owned model supported by equity financing (e.g., Chanel Japan) has guaranteed the brand’s premium ability. The study proposes a risk-stratified financing framework, recommending the use of equity crowdfunding and localized debt instruments in high-volatility markets, and strengthening capital resilience through contractual provisions (anti-dilution, exchange rate hedging).